Ração extrusada com diferentes relações volumoso: concentrado para ovinos em crescimento - Oliveira, Karla Alves (2018)
The provision of total ration to the animals favors a better roughage: concentrated -+985 ratio, preventing the animal from establishing an undesired proportion between the food and ensuring that it meets its nutritional requirement for maintenance and production. The objective was to compare the intake and digestibility of dry matter and nutrients, and the productive and physiological performance of lambs fed with extruded ration in different roughage (R): concentrated (C) ratios, being 30R:70C and 70R: 30C. The experiment was carried out at the Federal University of Uberlândia (UFU), Experimental Farm Capim Branco, between October 2016 and February 2017. For the study of consumption and digestibility were used 10 lambs, mixed races (Santa Inês x Dorper), aged between four and five months, and mean weight of 25 kg. The animals were placed in metabolic cages equipped with feeder, drinking fountain, salt shaker and wooden slatted floor. The treatments consisted of extruded ration in 30R: 70C and 70R: 30C ratios, completely randomized to two treatments and five replicates. The means of treatments were evaluated by the Tukey test at a significance level of 5%. Consumption and digestibility of dry matter and nutrients, water consumption by animals, and nitrogen balance were analyzed. The 30R: 70C treatment showed lower intake of dry matter, crude protein, neutral detergent fiber, acid detergent fiber, hemicellulose and total digestible nutrients, and presented higher dry matter and neutral detergent fiber digestibility. It also presented lower intake and faecal excretion of nitrogen, consequently establishing a greater relation between nitrogen retained and ingested nitrogen. For the study of productive and physiological performance, 30 lambs were used, with age of three months and average weight of 20kg. The animals were allocated in collective stalls, being six stalls with five animals each, with a feeder, drinking fountain, salt shaker and suspended wooden floor. The treatments consisted of extruded ration in 30R: 70C and 70R: 30C ratios, completely randomized to two treatments and 15 replicates. The means of the treatments were evaluated by the Tukey test and a regression study at the significance level of 5%. The dry matter intake, ingestive behavior, ruminal movement, body growth, weight gain, ultrasound carcass evaluation, concentration of energy metabolic, protein and mineral metabolites, and blood concentration of enzymes that indicate hepatic and muscular activity were analyzed. There was lower CMS for 30R: 70C treatment, and reduction of CMS relative to body weight at the end of the experiment. The animals presented a reduction in the time spent with rumination and total chewing and also lower ruminal movement for the two rations analyzed during the experimental period. However, at the beginning of the experiment there was less time spent with rumination and total mastication for the 30R: 70C treatment. Regarding energetic metabolites, there was difference only for the analyzed period with reduction of cholesterol and consequent increase of HDL (high density lipoprotein), as well as reduction in fruits at the end of the experimental period. There was interaction between treatment and time of evaluation for glucose concentration, and reduction of this metabolite at the end of the experimental period. On protein metabolites only urea was affected by treatments with higher concentration in the animals consuming the extruded ration with higher concentrate content. Liver enzymes aspartate aminotransferase (AST) and alkaline phosphatase were influenced by the evaluation period, with AST increased linearly positive and alkaline phosphatase decreased at the end of the experimental period, while gamma globulin (GGT) was interacted between treatments and evaluation period. The mineral metabolites phosphorus and calcium had a reduction of their concentrations at the end of the experimental period, and the phosphorus had a higher concentration in the treatment with 70% of roughage. It was observed a quadratic effect for growth variables height of the posterior, height of the anterior, body length, chest circumference and barrel, indicating that the animals presented adequate body growth, with intense development during the experimental period and stabilization at the end of the experiment. There was no difference in the animals weight gain, with the average daily gain of 182.79 g/day. Regarding the carcass evaluation, a difference was observed in the evaluation period, with a larger loin eye area, body condition score and subcutaneous fat thickness at the end of the experimental period.